Molecular diagnosis of heterozygosity loss for 1p/19q in oligodendroglial tumors by multiplex PCR at the National Institute of Neoplastic Diseases, Lima-Peru. - Murguía-Cuadros, Jimena (2019)
A heterozygosity loss of 1p/19q has clinical prognostic value and is strongly associated with classical histologic features of oligodendroglioma. Objectives: The present article proposes a molecular method to determine the loss of heterozygosity (LOH) for 1p/19q and to allow the classification of oligodendroglial tumors. Material and Methods: Fresh samples from the National Institute of Neoplastic Diseases Tumor BioBank and paraffin-embedded tissue biopsies of oligodendroglial tumors with pathological diagnosis of oligodendroglioma and oligoastrocytoma were used. The proposed methods are Multiplex PCR and amplification of fragments by capillary electrophoresis of PCR products, and were applied to a total of 39 cases which presented histological grade II and III. Results: The results obtained allow an adequate molecular classification of oligodendroglial tumors.